The Effect of Gross Domestic Product, Energy Consumption and Forest Area on Carbon Dioxide Emissions in ASEAN-5 - Adha , Isni Syafhira; Azwardi (Journal of Economic Development, Environment and People, 2023)
Due to human activity-related carbon dioxide emissions, the earth’s temperature has increased, resulting in climate change and global warming. The anomaly of climate change, which raises the global average temperature, has shown that environmental damage is genuine. In five ASEAN nations—Indonesia, Thailand, Malaysia, Singapore, and the Philippines—between 2001 and 2020, this study will examine the impact of GDP, energy use, and forest area on carbon dioxide emissions. This study’s methodology combined quantitative descriptive analysis with panel data regression analysis. The findings indicate that forest area and gross domestic product have a negative and considerable impact on carbon dioxide emissions. Consequently, carbon dioxide emissions are positively and significantly impacted by energy usage.